Barium titanate microspheres by low temperature hydrothermal method: studies on structural, morphological, and optical properties. Issue 1 (2nd January 2018) - Kothandan, D.; Jeevan Kumar, R.; Chandra Babu Naidu, K.
ABSTRACT: The barium titanate (BT) microspheres were synthesized via the low temperature hydrothermal technique. The X-ray diffraction pattern confirmed the formation of cubic perovskite structure of the material. The average crystallite size (Dp ) was found to be of 21 nm using the Scherrer method. The Williamson–Hall plot was drawn for evaluating the micro-strain and crystallite diameter. The relation between micro-strain (ε) and Dp was illustrated as a function of diffraction angle (2θ). The morphology was analyzed by field emission and transmission electron microscope. The results expressed the formation of microspheres. In addition to these, the optical bandgap (Eop ) and maximum absorption wavelength (λm ) were achieved to be of 3.23 eV and 340 nm, respectively. The presence of metal oxide bonds (M-O) was observed which in turn attributes the formation of cubic structure.